2010
DOI: 10.1177/0734016810373114
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Politics of Punishment: A Contextual Analysis of Racial Disparity in Drug Sentencing

Abstract: This study uses Tobit to assess contextual punishment determinants for a large sample of felony drug cases that reached final disposition in 1990. After statistically holding constant ascribed and legal variables, the authors find that punishments for African American defendants in drug-related cases varied by social and political context. African American defendants adjudicated in jurisdictions characterized by a large Black population received reduced punishments; but in jurisdictions that were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…The data underlying this analysis do not allow any more detailed insight regarding this possibility. However, the sentencing research seems to support this speculation since many researchers have argued that judges and prosecutors share the underlying values of their constituents and are typically elected and/or must stand for re-election (Helms & Jacobs, 2002;Helms, 2009;Helms & Costanza, 2010). This ever-present reality may be expected to shape the courtroom calculus concerning offenders so that in the most politically conservative jurisdictions judges and prosecutors lean more strongly toward incarceration.…”
Section: International Journal Of Social Science Researchmentioning
confidence: 97%
See 2 more Smart Citations
“…The data underlying this analysis do not allow any more detailed insight regarding this possibility. However, the sentencing research seems to support this speculation since many researchers have argued that judges and prosecutors share the underlying values of their constituents and are typically elected and/or must stand for re-election (Helms & Jacobs, 2002;Helms, 2009;Helms & Costanza, 2010). This ever-present reality may be expected to shape the courtroom calculus concerning offenders so that in the most politically conservative jurisdictions judges and prosecutors lean more strongly toward incarceration.…”
Section: International Journal Of Social Science Researchmentioning
confidence: 97%
“…Drug offending has been the focus of political discourse throughout the past 40 years, and has been suspected as a key source of growing prison populations (Helms & Costanza, 2010) and other social control processes (Helms & Costanza, 2009). We proxy for the level of drug offending with an indicator of police drug arrests.…”
Section: F Drug Offending and Reentry Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, research finds that conservative political climates are associated with expansions in prison admissions (Jacobs & Helms, 1996, 2001; Jacobs & Jackson, 2010) and spending on corrections (Jacobs & Helms, 1999; Jacobs & Jackson, 2010). Moreover, quite often, political context interacts with individual-level offender characteristics, such as race/ethnicity and sex, to explain variation in criminal justice outcomes (Helms & Costanza, 2010; Helms & Jacobs, 2002). For example, Helms and Jacobs (2002) found that African Americans and males tend to receive more punitive sanctions when they are sentenced in courts embedded within conservative political climates.…”
Section: Social Context and Sentencingmentioning
confidence: 99%
“…Scholars offer several explanations, including differential exposure to police surveillance [ 9 ], prosecutorial discrimination [ 11 ], the use of incarceration to deal with a ‘racial threat’ [ 12 , 13 ] or sentencing disparities between Blacks and Whites. Although studies reveal that racial sentencing disparities are reduced when legal factors [ 14 16 ] or social contexts [ 17 , 18 ] are considered, a recent meta-analysis reports that sentencing disparities remain even after controlling for these factors [ 4 ]. While the magnitude of the difference is small and variable, it is largest in cases involving discretionary powers and for drug offences.…”
Section: Introductionmentioning
confidence: 99%